Predictors and portfolios over the life cycle: Skill vs. luck - Holger Kraft; Claus Munk; Farina Weiss (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
In a calibrated consumption-portfolio model with stock, housing, and labor income predictability, we disentangle the welfare effects of skill and luck. Skilled investors are able to take advantage of all sources of predictability, whereas unskilled investors ignore predictability. Lucky investors enter the market at a favorable time. For an unskilled investor the certainty equivalent of wealth is 0.3-6.8% lower than for a skilled investor, depending on the market entry date. Across market entry dates, skilled but unlucky investors can lose up to 15.4% compared to unskilled but lucky investors. Simulation studies confirm the relative importance of luck and document that, if anything, housing predictability is more important than stock predictability.
Keywords: G11; D91; D14; 330; Return predictability; scenarios; welfare; performance; housing